2000
DOI: 10.1086/317063
|View full text |Cite
|
Sign up to set email alerts
|

Optical Spectrum of Main‐, Inter‐, and Off‐Pulse Emission from the Crab Pulsar

Abstract: A dedicated stroboscopic device was used to obtain optical spectra of the Crab main-pulse and inter-pulse as well as the spectrum of the underlying nebula when the pulsar is turned off. As the nebular emission is very inhomogeneous, our ability to effectively subtract the nebular background signal is crucial.No spectral lines intrinsic to the pulsar are detected. The main-pulse and the inter-pulse behave as power laws, both with the same de-reddened index α = +0.2 ± 0.1. This value was obtained by subtracting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…Significant variations are apparent, especially in the B/V data, but after dividing out the predicted variations due to pile-up, there is no longer any strong evidence for colour changes across the pulse profile. This is consistent with previous studies in the UV-optical-IR band, which have reported either no colour changes (e.g., Carramiñana et al 2000), or very slight ones (e.g., Eikenberry et al 1996, Romani et al 2001. This suggests that the pile-up characteristics of S-Cam2 are well understood, at least in the count rate regime probed by the Crab.…”
Section: Spectral Distortion Due To Pile-upsupporting
confidence: 92%
“…Significant variations are apparent, especially in the B/V data, but after dividing out the predicted variations due to pile-up, there is no longer any strong evidence for colour changes across the pulse profile. This is consistent with previous studies in the UV-optical-IR band, which have reported either no colour changes (e.g., Carramiñana et al 2000), or very slight ones (e.g., Eikenberry et al 1996, Romani et al 2001. This suggests that the pile-up characteristics of S-Cam2 are well understood, at least in the count rate regime probed by the Crab.…”
Section: Spectral Distortion Due To Pile-upsupporting
confidence: 92%
“…The absence of this feature is also noted by Sollerman et al (2000) and Carramiñana et al (2000). Is the result of Nasuti et al then wrong?…”
Section: Resultsmentioning
confidence: 87%
“…Its consequences might have appeared 1.5 years later during the observations of Nasuti et al (1996). The observations of Carramiñana et al (2000) were conducted 18 days after the glitch in October 1999, but here the frequency jump and the relaxation time were close to a minimum.…”
Section: Resultsmentioning
confidence: 96%
“…We estimate the number distribution of photons detected as a function of wavelength in order to determine our effective observing wavelength. The spectrum of the Crab Pulsar at optical and near-infrared wavelengths is known to follow an empirically-measured power law (Carramiñana et al 2000). Using MODTRAN (Berk et al 1987) to estimate the transmission of the atmosphere due to Rayleigh scattering and telluric absorption, and taking into account the manufacturer-provided transfer functions of each optical component (two achromatic lenses, a detector quantum efficiency curve, as well as a pair of dichroic beamsplitters), we are able to compute up to an overall multiplicative constant the underlying number distribution versus wavelength of the Crab photons detected.…”
Section: Observations Of the Crab Pulsarmentioning
confidence: 99%